Effects of phosphodiesterase 4 inhibition on bleomycin-induced pulmonary fibrosis in mice - Udalov, Sergey; Justus Liebig University Giessen (My University, 2009)
Pulmonary fibrosis (PF) is an irreversible and largely untreatable human disease with the causes often remaining unknown. Phosphodiesterase 4 (PDE4) is involved in the processes of inflammation, cell proliferation, differentiation and migration that are known to play an important role in tissue fibrosis. The aim of the study was, therefore, to determine the expression of PDE4 under conditions of PF and to investigate the effects of PDE4 inhibition on functional, histological and biochemical parameters in experimental PF.Pulmonary fibrosis was induced by cytostatic and profibrotic agent bleomycin in C57BL/6N mice. Expression profiles of the different PDE4 isoforms were analyzed at mRNA and protein levels in lungs with both experimental and human PF. Animals were treated with the selective PDE4 inhibitor cilomilast and/or vehicle and treatment effects were examined by means of bronchoalveolar lavage fluid (BALF) differential cell count, mRNA analysis for lung tumor necrosis factor (TNF)-alpha, interleukin (IL)-1beta, IL6, pulmonary compliance measurement, quantified pathological examination of the lungs, collagen assay and survival analysis.Analysis of PDE4 expression showed significant upregulation of inflammation-related PDE4 isoform in lungs with both human and experimental PF. Treatment of mice with cilomilast resulted in significant reduction in total number of cells, number of macrophages and lymphocytes, but not neutrophils, in BALF at early inflammatory fibrosis stage (days 4 and 7). Lung TNFalpha, but not IL1beta, level was also significantly reduced by cilomilast while level of IL6 was significantly elevated. At later stage (days 14 and 21) cilomilast-treated mice demonstrated improved lung function and lesser fibrosis degree compared to non-treated group. Lung collagen content and overall survival were also partially restored by treatment with cilomilast.Our results suggest that selective PDE4 inhibition suppresses early inflammatory stage and has the potential to attenuate the late stage of pulmonary fibrosis in experimental fibrosis and thus may offer a new therapeutic option for patients with PF.

Die Lungenfibrose ist eine progressive und meistens tödliche Erkrankung, für die es noch immer keine effektive Behandlung gibt. Die Phosphodiesterase 4 (PDE4) spielt bei verschiedenen zellulären Prozessen wie Entzündung, Proliferation, Differenzierung und Migration eine wichtige Rolle. Das Ziel der vorliegenden Arbeit war die Untersuchung der Rolle der PDE4 in der experimentellen Fibrose. Dazu erfolgten Untersuchungen zur Expression der PDE4 in fibrotischen Lungen und Überprüfung des Effektes einer PDE4-Hemmung auf funktionelle, histologische und biochemische Parameter in einem experimentellen Modell der Fibrose.Dazu wurde eine Lungenfibrose in C57BL/6N Mäusen durch eine einmalige Gabe von Bleomycin induziert und die Expression der verschiedene PDE4 Isoformen auf mRNA- und Proteinebene bestimmt. Die Versuchstiere wurden weiterhin mit dem selektivem PDE4-Hemmstoff Cilomilast oder mit dem Placebo behandelt. Anschließend wurden die Behandlungseffekte durch Zellzählung der bronchoalveolären Lavage (BAL), Genexpressionsanalyse der Zytokine Tumor-Nekrose-Faktor (TNF) alpha, Interleukin (IL) 1beta, IL6, pulmonale Compliance-Messung, quantifizierte pathologische Lungenuntersuchung, Kollagenanalyse und die Überlebensdauer untersucht. Begleitende Untersuchungen zur Expression der PDE4 Isoformen erfolgten am explantierten Gewebe von Patienten mit Lungenfibrose.Die Genexpressionsanalyse der PDE4 zeigte eine signifikant erhöhte Expression der entzündungsbedingten Isoformen in Maus- und Humanlunge mit Lungenfibrose. Die Behandlung mit Cilomilast führte zu einer signifikanten Reduktion der totalen Zellnummer, der Nummer von Makrophagen und Lymphozyten, nicht aber der Neutrophilien, in der BAL in der frühen Krankheitsphase (Tage 4 und 7). Der Zytokinspiegel von TNFalpha wurde signifikant gesenkt, während die Spiegel von IL1beta und IL6 unverändert blieben. In der späteren Krankheitsphase (Tage 14 und 24) zeigten die Cilomilast-behandelten Mäuse eine verbesserte Lungenfunktion und weniger Fibrose, im Verglech mit unbehandelte Tieren.Zusammenfassend kann man sagen, dass im experimentellen Modell der Lungenfibrose eine selektive Hemmung der PDE4 die frühe Entzündungsreaktion unterdrückt und möglicherweise die spätere Krankheitsphase abschwächt. Dies könnte daher eine neue Behandlungsmöglichkeit zur Therapie der Lungenfibrose darstellen.
Effekte einer Phosphodiesterase 4-Hemmung im Bleomycin-induzierten Modell der Lungenfibrose in Mäusen
Keywords: ddc:610